Pressure safety design practices for refinery and chemical operations - Cheremisinoff, Nicholas P. (Noyes Publications, 1998)
Pressure Safety Design Practices for Refinery and Chemical Operations is an introductory reference guide for pressure relieving operations in petroleum refineries and chemical plants. Petroleum refineries and their related chemical manufacturing facilities often operate at high pressures and/or at conditions that can result in excessive pressure conditions. Start-up and emergency shut-down operations, transient upset conditions, or catastrophic equipment failures, as well as plant process fires and plant wide utility failures, all require fail safe systems that will alleviate high process operating conditions in a safe and expedient manner.